A modified formula using energy system contributions to calculate pure maximal rate of lactate accumulation during a maximal sprint cycling test - Yang, Woo-Hwi; Park, So-Young; Kim, Taenam; Jeon, Hyung-Jin; Heine, Oliver; Gehlert, Sebastian (Frontiers in Physiology, 2023)
Purpose: This study aimed at comparing previous calculating formulas of maximal lactate accumulation rate (νLa.max) and a modified formula of pure νLa.max (PνLa.max) during a 15-s all-out sprint cycling test (ASCT) to analyze their relationships. Methods: Thirty male national-level track cyclists participated in this study (n = 30) and performed a 15-s ASCT. The anaerobic power output (Wpeak and Wmean), oxygen uptake, and blood lactate concentrations (La−) were measured. These parameters were used for different calculations of νLa.max and three energy contributions (phosphagen, WPCr; glycolytic, WGly; and oxidative, WOxi). The PνLa.max calculation considered delta La−, time until Wpeak (tPCr−peak), and the time contributed by the oxidative system (tOxi). Other νLa.max levels without tOxi were calculated using decreasing time by 3.5% from Wpeak (tPCr −3.5%) and tPCr−peak. Results: The absolute and relative WPCr were higher than WGly and WOxi (p < 0.0001, respectively), and the absolute and relative WGly were significantly higher than WOxi (p < 0.0001, respectively); νLa.max (tPCr −3.5%) was significantly higher than PνLa.max and νLa.max (tPCr−peak), while νLa.max (tPCr−peak) was lower than PνLa.max (p < 0.0001, respectively). PνLa.max and νLa.max (tPCr−peak) were highly correlated (r = 0.99; R2 = 0.98). This correlation was higher than the relationship between PνLa.max and νLa.max (tPCr −3.5%) (r = 0.87; R2 = 0.77). νLa.max (tPCr−peak), PνLa.max, and νLa.max (tPCr −3.5%) were found to correlate with absolute Wmean and WGly. Conclusion: PνLa.max as a modified calculation of νLa.max provides more detailed insights into the inter-individual differences in energy and glycolytic metabolism than νLa.max (tPCr−peak) and νLa.max (tPCr −3.5%). Because WOxi and WPCr can differ remarkably between athletes, implementing their values in PνLa.max can establish more optimized individual profiling for elite track cyclists.